Lysosome-targeted photodynamic treatment induces primary keratinocyte differentiation - Daugelavičienė, Neringa; Grigaitis, Pranas; Gasiule, Liepa; Dabkeviciene, Daiva; Neniskyte, Urte; Sasnauskiene, Ausra (Journal of photochemistry and photobiology. B, Biology, 2021)
Photodynamic therapy is an attractive technique for various skin tumors and non-cancerous skin lesions. However, while the aim of photodynamic therapy is to target and damage only the malignant cells, it unavoidably affects some of the healthy cells surrounding the tumor as well. However, data on the effects of PDT to normal cells are scarce, and the characterization of the pathways activated after the photodamage of normal cells may help to improve clinical photodynamic therapy. In our study, primary human epidermal keratinocytes were used to evaluate photodynamic treatment effects of photosensitizers with different subcellular localization. We compared the response of keratinocytes to lysosomal photodamage induced by phthalocyanines, aluminum phthalocyanine disulfonate (AlPcS2a) or aluminum phthalocyanine tetrasulfonate (AlPcS4), and cellular membrane photodamage by m-tetra(3-hydroxyphenyl)-chlorin (mTHPC). Our data showed that mTHPC-PDT promoted autophagic flux, whereas lysosomal photodamage induced by aluminum phthalocyanines evoked differentiation and apoptosis. Photodamage by AlPcS2a, which is targeted to lysosomal membranes, induced keratinocyte differentiation and apoptosis more efficiently than AlPcS4, which is targeted to lysosomal lumen. Computational analysis of the interplay between these molecular pathways revealed that keratin 10 is the coordinating molecular hub of primary keratinocyte differentiation, apoptosis and autophagy.